Red Ear Fungi (Auricularia Auricula) Infusion Reduce Blood Triglyceride Level in Dyslipidemic Rats - Widi, Nareswara Anugrah; Sitorus, Truly D.; Rita, Coriejati (Althea Medical Journal, 2015)
Background: Dyslipidemia is a risk fastor in atherosclerosis. In the long run, it can cause complications such as coronary artery disease and stroke. Dyslipidemia can be halted by beta glucan, a soluble fiber found in some species of fungi. This study was conducted to find the effect of red ear fungi infusion in reducing blood triglyceride level and the concentration that will give optimal reduction of blood triglyceride level.Methods: This was an analytical study using experimental laboratoric method. The study conducted in 25 male Wistar rats sorted in 5 groups during the period of September to October 2012 in Pharmacology Laboratory of General Hospital Hasan Sadikin, Bandung.Results: The result showed that mean difference of all three treatment group, which is group 3, group 4, and group 5 (87.08, 90.40, and 82.70 respectively) showed significancy compared to the positive control (group 2). Out of the three group, group 4 with 36% infusion concentration has the lowest mean difference from all of the treatment groups.Conclusions: Red ear fungi infusion reduce blood triglyceride level and infusion with 36% concentration was the optimal concentration in reducing blood triglyceride level. A further study can be done to find concentration range in which the infusion reduce blood triglyceride level optimally.Key words: beta glucan, red ear fungi infusion, triglyceride